A DFT and TD-DFT Study of Two Hydralazine Derivatives for Organic Solar Cells and Nonlinear Optical Applications - Remi Nkeih Tamighang; Dodo Lydie Ajifack; Stanley Numbonui Tasheh; Nyiang Kennet Nkungli; Charly Tedjeuguim Tsapi; Julius Numbonui Ghogomu (Journal of Chemistry)
In recent years, organic molecules have been the subject of in-depth research studies using in silico methods for their applications in solar cells and photonic devices. This study reports a theoretical investigation of the organic solar cell (OSC) and nonlinear optical (NLO) properties of (E)-1-(phthalazin-1-yl)-1-[(pyridin-2-yl)ethylidene]hydralazine (PPEH) and 1-[2-(1-(pyridine-3- yl)ethylidene)hydrazinyl]phthalazine (PEHP). The density functional theory (DFT) and its time-dependent extension (TD-DFT) were employed with the B2PLYP, M06-2X, BP86, CAM-B3LYP, and ω B97-XD functionals, alongside the def2-tzvp and def2-tzvpp basis sets. Geometrical and Frontier molecular orbital (FMO) analyses were performed. Reactivity descriptors, open circuit voltage (Voc), energy driving force (∆EL−L), light harvesting efficiencies (LHEs), NLO susceptibilities, and properties were also computed and discussed. The results show that PEPH and PPEH are good electron donor materials for organic solar cells as they possess high FMO energies, Vocs, ∆EL−Ls, and LHEs. Moreover, both molecules have static first and second hyperpolarizabilities as well as dynamic NLO responses that are on average 10 times greater than those of para-nitroaniline. PEPH and PPEH also exhibit properties such as second harmonic generation (SHG), electro-optic Pockels effect (EOPE), electric field-induced second harmonic generation (EFISHG), and optical Kerr effect (OKE). Indeed, these molecules are potential candidates for organic solar cells and NLO applications. Findings from this work may further accelerate the synthesis and development of green energy materials for optical solar cells and NLO applications in the future.